Information disclosure in e-commerce: A systematic review and agenda for future research - Kolotylo-Kulkarni, Malgorzata; Xia, Weidong; Dhillon, Gurpreet (Journal of business research, 2021)
Consumers disclose their private information to merchants when shopping online or responding to marketing campaigns despite their privacy concerns. Such disclosure is invaluable for business; thus, it is crucial to understand why, how, and with what outcomes consumers decide to share their information. However, extant evidence on this topic remains fragmented and inconclusive. This study aims to establish how information disclosure in e-commerce has been defined, consolidate and systematize extant evidence on it, review conceptual foundations and methodologies, and provide recommendations for further research. Therefore, we conduct a review of studies on disclosure in e-commerce and provide a synopsis of its dimensions, antecedents, and consequences. Our analysis reveals insights on how disclosure is studied and the elements that play a role in it. To help set directions for future research, we present an integrated theoretical model and a set of propositions regarding consumers’ disclosure in e-commerce.